Optimalisasi Pemasaran Digital dalam Meningkatkan Adopsi Perangkat Lunak Pemantau Produktivitas pada PT XYZ - Ali Akbar Lubis; Belferik, Ronald; Ariwibowo, Suminar; Riche, Riche; Pratama, Yudhistira Adhitya (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
In 2019, the trend of work-from-home or remote working began to be adopted by several companies in Indonesia. Along with this trend, there was a growing need for software that could monitor the performance of remote employees, one of which was Aplikasi ABC. To increase the adoption of this software, a digital marketing strategy based on observation was implemented, where its effectiveness was analyzed using data obtained from various marketing channels. This activity focuses on several online marketing strategies applied to enhance engagement, conversion rates, and brand awareness. The initial goal of the digital marketing campaign was to achieve an engagement and click-through rate of 5% of total impressions. However, by the end of 2019, the achieved rate was only 2.35%, primarily due to factors such as low brand awareness, less appealing ad designs, and ineffective headlines that failed to capture the target audience’s attention. Additionally, the campaign aimed for a 10% monthly increase in impressions with a marketing budget of less than IDR 5,000,000 per month. The analysis results indicate that advertising costs, SEO optimization, and landing page content quality significantly influence engagement growth and user conversion rates. From this activity, it can be concluded that a more effective digital marketing strategy requires optimized audience targeting, improved ad design quality, and the utilization of more targeted marketing channels. Moreover, well-optimized websites and landing pages can enhance customer retention and support successful user acquisition. These findings can serve as a foundation for developing more effective digital marketing strategies in the future.